A broadband cavity-enhanced spectrometer for atmospheric aerosol light extinction measurements. Issue 11 (2nd November 2021) - John, Shebin; Wang, Meng; Chen, Jun; Pakkatil, Anoop; Du, Yingying; Zhang, Jialuo; Ramachandran, Arun; Saseendran, Aiswarya; Thomas, Arun P.; Viswanathan, Deepa; Mazzoleni, Claudio; Varma, Ravi
Abstract: Broadband optical cavity spectroscopy is considered as a technology for trace gas detection; however, recently this has been used for the retrieval of extinction coefficients of aerosols. In this study, we introduce an Incoherent Broadband Cavity Enhanced Extinction spectrometer (IBBCEES), spanning a spectral range from 400–550 nm, which was used to measure the broadband extinction coefficient of ambient aerosols and its temporal variations. Experiments were carried out as a part of an atmospheric field measurements campaign in Yangtze River Delta conducted during summer of 2019 in Changzhou, Jiangsu province, P. R. China. The size distributions and wavelength dependent absorption coefficients of aerosols were measured using a scanning mobility particle sizer (SMPS) and an absorption spectrometer (Aethalometer-AE33), respectively. During the study, it was observed that the temporal variations of measured broadband extinction coefficients and absorption coefficients exhibited a similar trend with the aerosol number density, measured by the SMPS. The spectral dependent single scattering albedo (SSA) derived using the measured extinction and absorption coefficients favorably compares with co-located Cavity Attenuated Phase Shift-ALBedo monitor (CAPS-ALB) operating at 530 nm. The IBBCEES is a simple, sensitive, and robust instrument that can be used to measure the light extinction coefficient of atmospheric aerosols with an estimated net accuracy of ∼6.7% and a 3σ precision of ∼15 Mm −1 . The net uncertainties estimated on the reported AAE, EAE and SSA values are ∼3.1%, ∼4.1% and ∼11%, respectively. Copyright © 2021 American Association for Aerosol Research